The Pathogenesis and Treatment of Emotion Dysregulation in Borderline Personality Disorder - Andreas Laddis (The Scientific World Journal)
Uncontrollable emotional lability and impulsivity are a paramount phenomenon of Borderline Personality Disorder (BPD). This paper aims to review theories that entertain emotion dysregulation as the core deficit of BPD and a key factor in the etiology of BPD, in order, then, to propose the author’s own theory, which arguably transcends certain limitations of the earlier ones. The author asserts that his psychodynamic theory explains the symptoms of BPD more thoroughly and it inspires a more parsimonious interpretation of brain imaging findings. In closing, the author draws implications of the proposed theory for clinical practice. He reports an efficacy study for treatment of emotion dysregulation based on that theory.